Moonshine - Christina Jones
Cleo Moon is starting life over again after a divorce. She lands a job as PA to Lady of the Manor - Mimi - having settled herself in a caravan in the sleepy little village of Lovers' Knot. But the trouble starts when the most beautiful boy in the world - Dylan - turns up on her doorstep drunk one night.